Cannabinoid as Beneficial Replacement Therapy for Psychotropics to Treat Neuropsychiatric Symptoms in Severe Alzheimer’s Dementia: A Clinical Case Report - Defrancesco, Michaela; Hofer, Alex (Frontiers in Psychiatry, 2020)
Alzheimer´s Dementia (AD) is a devastating neurodegenerative disease that affects approximately 17 percent of people aged 75-84. Neuropsychiatric symptoms (NPS) such as delusions, agitation, anxiety, and hallucinations are present in up to 95% of patients in all stages of dementia. To date, any approved and effective pharmacological interventions for the treatment of NPS are still not available. We describe a clinical case of a female patient diagnosed with AD with continuous cognitive decline and dementia-related behavioural symptoms. Between 2008 and 2019, the patient was examined half-yearly at the memory clinic of the Medical University of Innsbruck. At each visit, cognitive state and pharmacological treatment were evaluated. In addition, neuropsychiatric symptoms were assessed by using the neuropsychiatric inventory (NPI). In 2018, the patient progressed to severe AD stage and presented with progressive neuropsychiatric symptoms (anxiety, suspected delusions, agitation, aggressive behaviour and suspected pain due to long immobility,). Consequently, off-label treatment with low-dose dronabinol was initiated, which facilitated a reduction of psychopharmacological treatment from six to three psychotropics. At the same time, the patient’s emotional state improved, while disruptive behaviour, aggression, and sedation decreased significantly. This case report underpins the need for randomized, controlled trials to explore the effect of cannabinoid receptor agonists on behavioural and psychological symptoms in patients with severe AD.